2013
DOI: 10.1128/jcm.01525-13
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Gen-Probe Aptima Qualitative HIV-1 RNA Assay for Diagnosis of Human Immunodeficiency Virus Infection in Infants

Abstract: The qualitative Roche HIV-1 DNA Amplicor assay has been used for the past 20 years to diagnose HIV infection in infants and young children but is being phased out; hence, alternative assays must be found. The Gen-Probe Aptima qualitative HIV-1 RNA assay is currently the only FDA-cleared HIV-1 nucleic acid assay approved for diagnosis, but data on the use of this assay with infant plasma are limited. We assessed Aptima's performance using control material for reproducibility and limit of detection and 394 plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…2021; 9(2):e105098. infection, and HIV-1 RNA in plasma samples is detectable earlier and is more reliable than HIV-1 proviral DNA in PBMC specimens of neonates with perinatal infection (19,30). Testing for HIV-1 RNA is more sensitive than the detection of HIV-1 proviral DNA for neonates younger than two months old, receiving prophylaxis with zidovudine syrup (8,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2021; 9(2):e105098. infection, and HIV-1 RNA in plasma samples is detectable earlier and is more reliable than HIV-1 proviral DNA in PBMC specimens of neonates with perinatal infection (19,30). Testing for HIV-1 RNA is more sensitive than the detection of HIV-1 proviral DNA for neonates younger than two months old, receiving prophylaxis with zidovudine syrup (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that HIV DNA PCR is significantly more sensitive than co-culture in the detection of HIV-1 in infected infants, and this method is recommended as the gold standard for virologic diagnosis of HIV infection in infants (1,19).…”
Section: Introductionmentioning
confidence: 99%
“…The qualitative Roche HIV-1 DNA Amplicor assay has been extensively used for EID and has been considered as the gold standard assay (8), although it has been phased out when new assays have been tested for EID of HIV-1 (9,10).…”
Section: Assays Evaluation For Hiv-eid Using Dbsmentioning
confidence: 99%
“…The Aptima HIV-1 RNA qualitative test (Hologic, Inc., San Diego, CA), a U.S. FDA-approved assay for molecular diagnosis of acute and primary HIV-1 infection, was selected for use in this study because of its claims of extreme sensitivity (14 copies/ml) and ability to detect the very earliest times of infection, with reported detection 12 days prior to that of enzyme immunoassay (EIA) repeat-reactive (RR) tests or 6 days prior to that of p24 antigen detection ( 24 , 25 ). This study evaluated the performance characteristics of the Aptima HIV-1 RNA assay and its ability to detect AHI by twice-weekly testing of small blood volumes (SBVs) from uninfected participants at high risk for HIV-1 infection.…”
Section: Introductionmentioning
confidence: 99%